2015
DOI: 10.1155/2015/680515
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Heart Rate Variability after Coronary Artery Bypass Grafting and Clinical Importance of These Findings

Abstract: Heart rate variability is a physiological feature indicating the influence of the autonomic nervous system on the heart rate. Association of the reduced heart rate variability due to myocardial infarction and the increased postinfarction mortality was first described more than thirty years ago. Many studies have unequivocally demonstrated that coronary artery bypass grafting surgery generally leads to significant reduction in heart rate variability, which is even more pronounced than after myocardial infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…However, they were in opposition to the results reported by Tseng et al [15], where the HRV parameters recorded before PCI procedure did not differ significantly from those assessed directly after the PCI procedure. Moreover, many studies have demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction, which is even more pronounced than after myocardial infarction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they were in opposition to the results reported by Tseng et al [15], where the HRV parameters recorded before PCI procedure did not differ significantly from those assessed directly after the PCI procedure. Moreover, many studies have demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction, which is even more pronounced than after myocardial infarction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14]. Unlike myocardial infarction where the main reason of the HRV reduction is ischaemia and myocyte necrosis, the probable reasons for considerable HRV reduction immediately after PCI or CABG include a combined effect of surgical manipulation during operative procedure on the heart and adjacent anatomical structures, prolonged anaesthesia [29,30] and cardioplegia [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The autonomic nervous system (ANS) has an important role in regulating physiological processes both in normal and pathological conditions [4, 5]. Individuals with AH typically have an ANS imbalance with greater performance and predominance of sympathetic ANS [68].…”
Section: Introductionmentioning
confidence: 99%
“…Heart activity is largely modulated by the autonomic nervous system, which promotes rapid adjustments in the cardiovascular system during different stimuli (i.e., physical exercise, mental stress and postural change) [1,2]. Heart rate variability (HRV) is a non-invasive measure used to analyze the influence of the autonomic nervous parasympathetic contributions to consecutive HR oscillations.…”
Section: Introductionmentioning
confidence: 99%